Designing play mats as a tool for gross motor stimulation for early childhood using design thinking - Rahman, Yanuar; Sintowoko, Dyah Ayu Wiwid (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2024)
The development of gross motor skills in early childhood is an important aspect of their initial growth stage. However, in the process of guidance, parents often face difficulties and limitations in stimulating their child's motor skills due to the lack of effective and adaptive play equipment. This research aims to address that gap by designing a practical play mat that can assist parents or institutions in supporting and stimulating the gross motor skills of early childhood children through design thinking steps. Qualitative research methods with a practice-based design approach were applied to develop a play tool that not only stimulates children's gross motor skills through movement but also supports social interaction and collaboration. The research results show that this tool facilitates parents and institutions in meeting children's gross motor development needs more effectively. These findings contribute in the form of practical and functional play mats, based on user-centered design, which can be applied in early childhood education institutions and family communities.